DAMPAK PERKEMBANGAN KERAJINAN KERAMIK TERHADAP KEHIDUPAN SOSIAL BUDAYA MASYARAKAT DI KANAGARIAN ANDALEH - Yuliarni Yuliarni; Anin Ditto (LP2M Universitas Sarjanawiyata Tamansiswa, 2017)
Progress of The ceramic crafts at Kanagarian Andaleh its have flux and reflux. One time the progress is very good, and at other times back down.These progress have effect on the economic, social and cultural life of the community in Kanagari Andaleh. The perceived economic effect can be seen through an improving life. The craftsmen began to enjoy the results of his work as a craftsman with a high enough value. The perceived social effect is a harmonious cooperation between artisans appear in the effort of mutual filling and learning in solving problems. Interaction between craftsmen always synergize, this is formulated in a more varied work. This interaction between craftsmen has a wide effect on enrichment of ideas and creativity on craftsmen. Ceramic crafts are often also used as indicators of social status strata in the community. This can be seen from the ceramic craft products used, both for the needs of secular life and spiritual life. High quality ceramic craft products will belong to people who have higher economic capability. In addition to investment goods, ceramic craft products will also affect the prestige and dignity of the people who have it.Keywords : Progress, ceramic